2012
DOI: 10.1111/j.1749-6632.2012.06600.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular players in the atherosclerotic plaque progression

Abstract: Atherosclerosis initiation and progression is controlled by inflammatory molecular and cellular mediators. Cells of innate immunity, stimulated by various endogenous molecules that have undergone a transformation following an oxidative stress or nonenzymatic glycation processes, activate cells of the adaptive immunity, found at the borders of atheromas. In this way, an immune response against endogenous modified antigens takes place and gives rise to chronic low-level inflammation leading to the slow developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Overexpression of both TNF-α and IL-6 was reported, amongst other syndromes and diseases, to cause cachexia, rheumatoid arthritis, and atherosclerosis [37-40]. Especially for production of TNF-α, intensive research has shown that stability and rate of translation of TNF-α mRNA is tightly regulated by various proteins [5, 12-14, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of both TNF-α and IL-6 was reported, amongst other syndromes and diseases, to cause cachexia, rheumatoid arthritis, and atherosclerosis [37-40]. Especially for production of TNF-α, intensive research has shown that stability and rate of translation of TNF-α mRNA is tightly regulated by various proteins [5, 12-14, 33].…”
Section: Discussionmentioning
confidence: 99%
“…9 Cumulatively, this has the effect of recruiting more monocytes into the coronary intima and of attracting smooth muscle cells from the media. 10 Although there has been an emphasis on the critical role of LDL modification before uptake by macrophages, alternative pathways for foam cell formation that do not depend on LDL modification have been described, including uptake of aggregated LDL and fluid phase pinocytosis. 11,12 Although the initial inflammatory response is inherently appropriate, it is ultimately maladaptive in advanced atherosclerosis largely caused by defective inflammation resolution, with persistent recruitment of monocytes that differentiate into proinflammatory macrophages (M1), rather than into alternatively activated macrophages (M2), which promote inflammation resolution.…”
Section: Role Of Lipoproteins and Inflammation In Atherosclerosismentioning
confidence: 99%
“…For this reason, a detailed understanding of which major contributing processes to an outcome are altered with pathology and the extent for which these are compensated is critical for developing appropriate therapeutic interventions. Failure to elucidate both the key sites of impairment and the compensatory mechanisms, as well as how these impact functional outcomes, has resulted in poorly targeted interventional measures.Although the existing literature contains extensive prior interrogation into the effects of atherosclerotic peripheral vascular disease on perfusion and performance outcomes in multiple model systems as well as the identification of many putative mechanistic contributors to plaque/lesion development (1,9,20,27,30,39), investigation into the impact of nonatherosclerotic peripheral vascular disease (PVD) has received a much more limited investment. Although underrepresented to date, this is an exceedingly important area of investigation, since a growing body of evidence suggests that an increasing number of human subjects are afflicted with the symptomology of PVD in the absence of overt plaque/lesion development (12,19,31,44,45).…”
mentioning
confidence: 99%